Direct synthesis of non-breathing MIL-53(Al)(ht) from a terephthalate-based ionic liquid as linker precursor - Fischer, Marcus; Schwegler, Johannes; Paula, Carolin; Schulz, Peter; Hartmann, Martin (Dalton Transactions, 2016)
An organic imidazolium salt of terephthalic acid has been utilized as a linker precursor for the synthesis of an aluminum-based metal organic framework (MOF) with MIL-53(ht) structure. This material shows the predicted porosity in terms of nitrogen and hydrogen sorption without exhibiting the breathing effect typical for MIL-53 (Al) materials.

Gluing Ionic Liquids to Oxide Surfaces: Chemical Anchoring of Functionalized Ionic Liquids by Vapor Deposition onto Cobalt(II) Oxide - Xu, Tao; Wähler, Tobias; Vecchietti, Julia; Bonivardi, Adrian; Bauer, Tanja; Schwegler, Johannes; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (Angewandte Chemie International Edition, 2017)
Ionic liquids (IL) hold a great potential as novel electrolytes for applications in electronic materials and energy technology. The functionality of ILs in these applications relies on their interface to semiconducting nanomaterials. Therefore, methods to control the chemistry and structure of this interface are the key to assemble new IL-based electronic and electrochemical materials. Here, we present a new method to prepare a chemically well-defined interface between an oxide and an IL film. An imidazolium-based IL, which is carrying an ester group, is deposited onto cobalt oxide surface by evaporation. The IL binds covalently to the surface by thermally activated cleavage of the ester group and formation of a bridging carboxylate. The anchoring reaction shows high structure sensitivity, which implies that the IL film can be adhered selectively to specific oxide surfaces.
Keywords: chemical anchoring; cobalt oxide; ester functionalization; ionic liquids; vapor deposition

Gluing ionic liquids to oxide surfaces: Chemical anchoring of functionalized ionic liquids by vapor deposition onto cobalt(II) oxide // Gluing Ionic Liquids to Oxide Surfaces: Chemical Anchoring of Functionalized Ionic Liquids by Vapor Deposition onto Cobalt(II) Oxide - Xu, Tao; Wähler, Tobias; Vecchietti, Ph. D. Maria Julia; Bauer, Tanja; Schwegler, Johannes; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (Angewandte Chemie, 2017)
Ionic liquids (IL) hold a great potential as novel electrolytes for applications in electronic materials and energy technology. The functionality of ILs in these applications relies on their interface to semiconducting nanomaterials. Therefore, methods to control the chemistry and structure of this interface are the key to assemble new IL-based electronic and electrochemical materials. Here, we present a new method to prepare a chemically well-defined interface between an oxide and an IL film. An imidazolium-based IL, which is carrying an ester group, is deposited onto cobalt oxide surface by evaporation. The IL binds covalently to the surface by thermally activated cleavage of the ester group and formation of a bridging carboxylate. The anchoring reaction shows high structure sensitivity, which implies that the IL film can be ``glued'' selectively specific oxide surfaces.
EAM Import::2019-03-13

Interaction of Ester-Functionalized Ionic Liquids with Atomically-Defined Cobalt Oxides Surfaces: Adsorption, Reaction and Thermal Stability - Xu, Tao; Wähler, Tobias; Vecchietti, Julia; Bonivardi, Adrian; Bauer, Tanja; Schwegler, Johannes; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (ChemPhysChem, 2017)
Hybrid materials consisting of ionic liquid (ILs) films on supported oxides hold a great potential for applications in electronic and energy materials. In this work, we have performed surface science model studies scrutinizing the interaction of ester-functionalized ILs with atomically defined Co3O4(111) and CoO(100) surfaces. Both supports are prepared under ultra-high vacuum (UHV) conditions in form of thin films on Ir(100) single crystals. Subsequently, thin films of three ILs, 3-butyl-1-methyl imidazolium bis(trifluoromethyl-sulfonyl) imide ([BMIM][NTf2]), 3-(4-methoxyl-4-oxobutyl)-1-methylimidazolium bis(trifluoromethyl-sulfonyl) imide ([MBMIM][NTf2]), and 3-(4-isopropoxy-4-oxobutyl)-1-methylimidazolium bis(trifluoromethyl-sulfonyl) imide ([IPBMIM][NTf2]), were deposited on these surfaces by physical vapor deposition (PVD). Time-resolved and temperature-programmed infrared reflection absorption spectroscopy (TR-IRAS, TP-IRAS) were applied to monitor insitu the adsorption, film growth, and thermally induced desorption. By TP-IRAS, we determined the multilayer desorption temperature of [BMIM][NTf2] (360 +/- 5K), [MBMIM][NTf2] (380K) and [IPBMIM][NTf2] (380K). Upon deposition below the multilayer desorption temperature, all three ILs physisorb on both cobalt oxide surfaces. However, strong orientation effects are observed in the first monolayer, where the [NTf2](-) ion interacts with the surface through the SO2 groups and the CF3 groups point towards the vacuum. For the two functionalized ILs, the [MBMIM](+) and [IPBMIM](+) interact with the surface Co2+ ions of both surfaces via the CO group of their ester function. A very different behavior is found, if the ILs are deposited above the multilayer desorption temperature (400K). While for [BMIM][NTf2] and [MBMIM][NTf2] a molecularly adsorbed monolayer film is formed, [IPBMIM][NTf2] undergoes a chemical transformation on the CoO(100) surface. Here, the ester group is cleaved and the cation is chemically linked to the surface by formation of a surface carboxylate. The IL-derived species in the monolayer desorb at temperatures around 500 to 550K.
Keywords: chemical anchoring; cobalt oxide; ionic liquids; IRAS; thermal stability

One-Step Synthesis of MIL-53(Al)/Boehmite Composites - Schwegler, Johannes; Fischer, Marcus; Paula, Carolin; Schulz, Peter; Hartmann, Martin (Chemie Ingenieur Technik, 2017)
[EMIM][Hbdc]and [EMIM](2)[bdc] were synthesized and successfully used in a one-step synthesis procedure of MIL-53(Al)/boehmite composites with unusual properties. The breathing effect typically observed for MIL-53(Al) is not found and scanning electron microscopy confirms the presence of MIL-53 nanoparticles in a boehmite matrix. The completely different characteristics of this MIL-53 samples in comparison to hydrothermally synthesized MIL-53(Al) clearly demonstrate the tremendous influence of variations of the reagents used for the syntheses of metal-organic framework materials.
Keywords: Ionic liquids; Metal-organic framework; NMR spectroscopy

Synthesis of the zeolitic imidazolate framework ZIF-4 from the ionic liquid 1-butyl-3-methylimidazolium imidazolate - Hovestadt, Maximilian; Schwegler, Johannes; Schulz, Peter; Hartmann, Martin (Journal of Chemical Physics, 2018)
A new synthesis route for the zeolitic imidazolate framework ZIF-4 using imidazolium imidazolate is reported. Additionally, the ionic liquid-derived material is compared to conventional ZIF-4 with respect to the powder X-ray diffraction pattern pattern, nitrogen uptake, particle size, and separation potential for olefin/paraffin gas mixtures. Higher synthesis yields were obtained, and the different particle size affected the performance in the separation of ethane and ethylene. Published by AIP Publishing.

Vacuum Surface Science Meets Heterogeneous Catalysis: Dehydrogenation of a Liquid Organic Hydrogen Carrier in the Liquid State - Matsuda, Takashi; Taccardi, Nicola; Schwegler, Johannes; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (ChemPhysChem, 2015)
Ultrahigh vacuum (UHV) surface science techniques are used to study the heterogeneous catalytic dehydrogenation of a liquid organic hydrogen carrier in its liquid state close to the conditions of real catalysis. For this purpose, perhydrocarbazole (PH), otherwise volatile under UHV, is covalently linked as functional group to an imidazolium cation, forming a non-volatile ionic liquid (IL). The catalysed dehydrogenation of the PH unit as a function of temperature is investigated for a Pt foil covered by a macroscopically thick PH-IL film and for Pd particles suspended in the PH-IL film, and for PH-IL on Au as inert support. X-ray photoelectron spectroscopy and thermal desorption spectroscopy allows us to follow in situ the catalysed transition of perhydrocarbazole to carbazole at technical reaction temperatures. The data demonstrate the crucial role of the Pt and Pd catalysts in order to shift the dehydrogenation temperature below the critical temperature of thermal decomposition.
Keywords: heterogeneous catalysis; ionic liquids; liquid organic hydrogen carrier; surface science; x-ray photoelectron spectroscopy